Prevalence of Polyneuropathy in Pre-Diabetes and Diabetes Is Associated With Abdominal Obesity and Macroangiopathy: The MONICA/KORA Augsburg Surveys S2 and S3 - Ziegler, Dan; Rathmann, Wolfgang; Dickhaus, Thorsten; Meisinger, Christa; Mielck, Andreas (Diabetes care, 2008)
OBJECTIVE:--It is controversial whether there is a glycemic threshold above which polyneuropathy develops and which are the most important factors associated with polyneuropathy in the general population. The aim of this study was to determine the prevalence and risk factors of polyneuropathy in subjects with diabetes, impaired fasting glucose (IFG), impaired glucose tolerance (IGT), or normal glucose tolerance (NGT). RESEARCH DESIGN AND METHODS--Subjects with diabetes (n = 195) and control subjects matched for age and sex (n = 198) from the population-based MONICA (Monitoring Trends and Determinants on Cardiovascular Diseases)/KORA (Cooperative Research in the Region of Augsburg) Augsburg Surveys 1989/1990 (S2) and 1994/1995 (S3) aged 25-74 years were contacted again and assessed in 1997/1998 by the Michigan Neuropathy Screening Instrument using a score cut point >2. An oral glucose tolerance test was performed in the control subjects. RESULTS:--Among the control subjects, 46 (23.2%) had IGT, 71 (35.9%) had IFG, and 81 had NGT. The prevalence of polyneuropathy was 28.0% in the diabetic subjects, 13.0% in those with IGT, 11.3% in those with IFG, and 7.4% in those with NGT (P <= 0.05 for diabetes vs. NGT, IFG, and IGT). In the entire population studied (n = 393), age, waist circumference, and diabetes were independent factors significantly associated with polyneuropathy, whereas in the diabetic group polyneuropathy was associated with age, waist circumference, and peripheral arterial disease (PAD) (all P < 0.05). CONCLUSIONS:--The prevalence of polyneuropathy is slightly increased in individuals with IGT and IFG compared with those with NGT. The association with waist circumference and PAD suggests that the latter and abdominal obesity may constitute important targets for strategies to prevent diabetic polyneuropathy.